A new data analysis framework for the search of continuous gravitational wave signals. (4th December 2018) - Piccinni, O J; Astone, P; D'Antonio, S; Frasca, S; Intini, G; Leaci, P; Mastrogiovanni, S; Miller, A; Palomba, C; Singhal, A
Abstract: Continuous gravitational wave signals, like those expected by asymmetric spinning neutron stars, are among the most promising targets for LIGO and Virgo detectors. The development of fast and robust data analysis methods is crucial to increase the chances of a detection. We have developed a new and flexible general data analysis framework for the search of this kind of signals, which allows to reduce the computational cost of the analysis by about two orders of magnitude with respect to current procedures. This can correspond, at fixed computing cost, to a sensitivity gain of up to 10%–20%, depending on the search parameter space. Some possible applications are discussed, with a particular focus on a directed search for sources in the Galactic center. Validation through the injection of artificial signals in the data of Advanced LIGO first observational science run is also shown.